Universal Skills Board - Syarunizam, Muhammad Nazmi; Khairulanuar, Muhammad Amirin Haikal; Mohd Zani, Muhammad Zamany Amni; Adnan, Cik Nor Faezah (Multidisciplinary Applied Research and Innovation, 2022)
Abstract: COVID-19 has had an impact on university education and has forced students to study online. In order to help the students to learn more deeply about the microcontroller subject, a universal kit which can help student to develop teaching aids specially for learning the basics of microcontroller and IoT. Blynk has three major components such as Blynk app, Blynk server and Blynk libraries. All component is connected together in Universal Skills Board and Proteus has been used to check the connection for the component and run the coding for the simulation. The code gives a command for the NodeMCU to give LED controlled by the Blynk app. The temperature sensor is useful for starting a monitoring system using the Blynk app. By using this universal skill board can help students understand and learn more deeply about the use of microcontrollers. Universal skills board also can be used with the blynk apps for creating IoT concept. By implementing the blynk, training modules has been developed to help students to use the Universal skills board more efficiently. In addition, to improve the performance of the universal skills board, this project can be improved by added a lot type of microcontroller sensor such as smoke and gas sensor, touch sensor and humidity sensor. By implementing the blynk, universal skills board also can develop home student skills to create and modify the coding and programming to connect the components to the blynk applications.